Perception of immigration and friendship with foreign pupil in secondary schools - de Miguel Luken, Verónica; Carvajal Gutiérrez, Carmen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
In this paper we present some of the most relevant findings obtained through a research on the opinion of students from several secondary schools in Málaga with an important presence of foreign pupils have about immigration. The association between these opinions and the existence of both positive and negative relationships among students from different geographical origins is also analyzed. The questionnaire that has been used for the fieldwork has focused on two main topics: friendship, mutual assistance and rejection networks, on one hand, and the view the adolescents manifest regarding the arrival of foreign population, on the other. The results show a clear correspondence between these young peoples’ judgments and those obtained through other surveys for the total Andalusian and Spanish population. However, they reveal a significant disparity between the prejudices towards the different immigrant groups and the affective and supportive relationships that, in fact, are established among classmates
Keywords: Foreign Immigration; Schools; Opinion; Social Network Analysis; Survey